Effect of Charge Eccentric Position on the Response of Reinforced Concrete Columns Under Blast Loading - Sihao Shen; Rongyue Zheng; Wei Wang; Chenzhen Ye (Buildings)
This study investigates the failure modes and damage extent of reinforced concrete (RC) columns under the combined action of eccentric blast loading and axial compressive loading through experimental tests and numerical simulations. Field blast tests were performed using half-scaled-down models for close-in airburst tests. The effects of charge mass, explosive position, and axial load on the failure modes and damage levels of RC columns under close-range blast loading were investigated. Eight experimental datasets of blast overpressure were obtained, and curve fitting was performed on these data to establish an empirical formula, thereby enhancing the predictive accuracy of blast effect assessment in practical engineering scenarios. The test results indicated that when the explosive position is closer to the column base, the structural failure mode becomes closer to shear failure. To further interpret the experimental data, a detailed finite element model of RC columns was developed. Numerical simulations of RC columns were conducted using the RHT model. The rationality of the model was validated through comparison with experimental data and the SDOF method, with dynamic response analyses performed on cross-sectional dimensions, the longitudinal reinforcement ratio, the scaled distance, the explosion location, and axial compression. An empirical formula was ultimately established to predict the maximum support rotation of RC columns. Studies have shown that when the explosive position is closer to the column base, the structural failure mode approaches shear failure, and axial compression significantly increases the propensity for shear failure.